Idealism in Geoffrey Chaucer’s“General Prologue” to The Canterbury Tales (Journal of the College of Education for Women, 2018)
The aim of this research is to analyze Chaucer’s use of idealism in the “General Prologue” to The Canterbury Tales. Idealism is defined as a belief that ideals are the only true reality. Therefore, it stresses the mental or spiritual over the material objects.Idealism is widely used during the Middle Ages, especially by Geoffrey Chaucer, who is England’s most famous poet. The Canterbury Tales is his masterpiece. This Research analyzes ideals in the “General Prologue” toThe Canterbury Tales.The conclusion of the present research shows that Chaucer uses idealism to criticize the follies and weaknesses of his age.Besides, he finds that adherence to ideal values is a means to cultivate morality leading to perfection.